Assessment of outcomes of newborns born to mothers with COVID-19 reverse transcription-polymerase chain reaction positivity before delivery in January 2022 ‐ A single center study from Eastern India - Sumana Kundragrami; Santanu Bag; Sunanda Dey; Jinia Saha (Asian Journal of Medical Sciences, 2023)
Background: There have been successive waves of SARS-CoV-2 variants since January 2020, the B.1.1.529 (Omicron) variant has led to a third upsurge in India since December 2021. Neonates constitute a vulnerable population and there is limited literature about natural history, management, and outcomes of Omicron infected newborns. Aims and Objectives: The study was conducted to study the outcomes among newborns born to COVID-19 positive mothers during the Omicron upsurge. Materials and Methods: Between December 2021 and January 2022, this study was conducted on newborns born to COVID-19 positive mothers in a single center during the Omicron upsurge. We investigated the maternal pregnancy complications, methods of delivery, neonatal resuscitation, neonatal conditions, suspicious infectious status, and morbidity based on maternal infections. Results: A total of 39 neonates were born to mothers with a history of Omicron COVID-19 infected during delivery. None were positive when tested or developed any disease specific symptoms in the postnatal period. Among the neonates, 5 needed admissions in newborn units. Birth asphyxia, transient tachypnea of the newborn and meconium aspiration syndrome was seen along with minor problems such as feed intolerance and hyperbilirubinemia. Rest all had been stable throughout the hospital course. All infants had been developmentally stable on followup up to 6 months post-discharge. Conclusion: During Omicron COVID-19, newborns had very less complications and we advise giving breast milk to babies with proper precautions along with rooming-in for the lower income countries.